?EFFECT OF EpOXIDES ON ULTRAVIOLET DEGRADATION OF POLYVINYL CHLORIDE (Biological Sciences - PJSIR, 1998)
PYC-DOP system was formulated with some prepared epoxidized vegetable oils such as epoxidized linseed and soybean oils aswell as epoxidized phenoliccompound such asthe preparedlow molecularweight bisphenol A diglycidyl ether. Ba/Pb laurate as a light stabilizer was added in low concentration. Samples without epoxidized compounds were also Formulated.The formulated PYC samples with and without a light stabilizer were tested and evaluated before and after exposure to UY lamp for 6 months at 20°C. The effect of these epoxidized compounds on colour, mechanical properties and electrical volume resistivity of PYC samples before and after exposure to UY radiation was studied. It was found that the epoxidized linseed and soybean oils were generally good both as stabilizers and plasticizers. While bisphenol A diglycidyl ether was generally a good stabilizer but poor plasticizer. The epoxidized samples were also evaluated for use in electrical insulation fields.